Upaya Peningkatan Kualitas Hidup Pasien ODHA Melalui Program Hospice Care Di Kecamatan Buleleng - Eka Lutfiatus Solehah; Yuly Peristiowati; Yenny Puspitasari (Jurnal Keperawatan Muhammadiyah, 2023)
ABSTRAK The purpose of the study was to analyze efforts to improve the quality of life of patients with HIV through the Hospice Care Program in Buleleng District. This research design is Quasy Experiment with Pretest and posttest approach with control group design. The study population was HIV / AIDS patients in the work area of Buleleng Kec. with a total of 90 patients. The sample in the study was taken by random sampling technique as many as 42 respondents for the experimental group and 42 respondents for the control group. data collected by questionnaire instrument and tested by paired t test. The results showed that there was an increase in the mean value in the experimental group of 29.976 so that these results were greater than the increase in the mean value in the control group = 23.167 so this shows that the Hospice care program is more effective in reducing the quality of life of respondents in Buleleng District. The paired t test results show the significance value of both groups ρ = 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, meaning that there is an improvement in the quality of life of PLWHA patients through the Hospice Care Program. The hospice care program is implemented by focusing more on patient psychological services so that the patient’s quality of life can improve.